Where does the money go to? Cost analysis of gynecological patients with a benign condition. - Kristiina Pynnä (Public Library of Science (PLoS), 2021)
Objectives The impact of benign gynecological conditions on life of women and on costs for the society is high. The purpose of this study is to gain knowledge and understanding of costs of the treatment of these disorders in order to be able to improve the clinical care processes, gain insight into feasible savings opportunities and to allocate funds wisely. Methods The healthcare processes of 311 women attending university or community hospitals in the Helsinki and Uusimaa Hospital District between June 2012 and August 2013 due to a benign gynecological condition were followed up for two years and treatment costs analysed. Results Total direct hospital costs averaged 689€ at six months and 2194€ at two years. The most expensive treatment was that of uterine fibroids in the short term and that of endometriosis and fibroids later on. Costs did not depend on hospital size. Surgical operations caused nearly half of hospital costs. Productivity loss caused biggest expenses outside of the hospital. LNG-IUD (levonorgestrel-releasing intrauterine device) accounted for the largest pharmaceutical costs for patients. Hospital treatment was associated with a reduced need for outpatient services during follow-up. Conclusions A majority of direct hospital costs arise over time. This stresses the need for prolonged healthcare management. To control costs, the need for repetitive doctors' appointments, monitoring tests, and ward treatments should be carefully evaluated. Procedures not needing an operation theatre (for example hysteroscopy for polypectomy), should be done ambulatorily.